Adsorption of 59Fe on glassware and its effect on data deduced. Issue 6 (November 1969) - Smith, Mary D.; Kernaghan, T.
Abstract : The attachment of 59 Fe to glassware under conditions of hospital laboratory procedure forms the subject of this communication. Adsorption of this nature can be extreme and can invalidate data derived or prejudice intended dose levels. It is aggravated by sterilization by autoclave. Data indicating the severity of the phenomenon are presented and methods of controlling it are discussed.